Residual/recurrent lesions after cold-knife conization for high-grade cervical intraepithelial neoplasia: risk factor analysis and clinical management recommendations - Wu, Chenchun; Guo, Peng; Huang, Pengchong; Guo, Lili; Xiong, Lili (Frontiers in Oncology, 2025)
ObjectiveThis study aims to evaluate the risk factors of residual/recurrent lesions of cervical intraepithelial neoplasia 2/3 (CIN2/3) in patients who underwent cold-knife conization (CKC).MethodsA total of 976 patients with CIN2/3 who were treated with CKC were retrospectively analyzed. Post-CKC follow-up involved a thin-prep cytology test (TCT) and human papillomavirus (HPV) tests. Residual/recurrent lesions after CKC (RLC) were defined as biopsy-proven CIN2/3 during follow-up, whereas residual lesions identified after a hysterectomy (RLH) were defined as lesions in patients who underwent a hysterectomy 1–6 months after CKC and were diagnosed with CIN 2/3, cervical carcinoma in situ or invasive cancer. Univariate analysis and multivariate logistic regression analyses were performed to evaluate the relationship among factors such as age, menopausal status, pregnancy, parity, transformation zone, the height of excision, glandular involvement, persistent HPV infection, HPV infection types (preoperative and postoperative), TCT test (preoperative and postoperative), postoperative margins, and endocervical curettage (ECC) results for RLC and RLH.ResultsDuring the follow-up period, 152/976 (15.57%) of the patients underwent a hysterectomy and the remaining 824 patients completed their continuous follow-up. Of these, 45/824 (5.46%) were diagnosed with RLC and 53/152 (34.87%) of the patients who underwent a hysterectomy were diagnosed with RLH. RLC was significantly associated with factors such as persistent HPV infection, HPV infection types (preoperative and postoperative), TCT test (6-month postoperative), postoperative margins, and ECC results (P < 0.05). Of these variables, persistent HPV infection, HPV 16/18 infection (preoperative), positive margins, TCT test ≥ ASC-US (6- month postoperative), and HPV 16/18 infection (6-month postoperative) emerged as independent risk factors for RLC (P < 0.05). In patients undergoing a hysterectomy, RLH was linked to the transformation zone, the height of excision, glandular involvement, HPV infection types (preoperative), TCT test (preoperative), postoperative margins, and ECC results (P < 0.05). HPV 16/18 infection (preoperative), transformation zone (type 3), positive margins, and positive ECC appeared to be independent risk factors for RLH (P < 0.05).ConclusionRisk factors associated with RLC and RLH must be considered when implementing targeted clinical interventions. Elongating the clinical follow-up period is of paramount importance, particularly for patients with high-risk factors; therefore, it is recommended that follow-up intervals be reduced. For patients with HPV16/18 infection, positive margins, and positive ECC, it is recommended that a hysterectomy be performed whenever necessary.